On a new haematophagous species of the genus Leptoconops (Holoconops) Kieffer (Diptera, Ceratopogonidae) from the coastal region of West Bengal, India - Lipika Ghosh; Gouri Sankar Pal; Niladri Hazra (Evolutionary Systematics)
Leptoconops (Holoconops) beccus sp. nov. is described from India after molecular and morphological data. Both sexes of the new species were fetched from Digha, the coastal region of West Bengal. A revised key to the Oriental species of the subgenus Holoconops Kieffer is also designed.